Rationales for First Nations Run Schools in Ontario : a Content Analysis - Hiona Murray (10858323) (2010)
The purpose of this research study was to address the question: how do First Nations leaders and scholars articulate the rationales for First Nations run schools in Ontario? Documents were collected from two First Nations websites, Assembly of First Nations and Chiefs of Ontario, and subjected to a manifest and latent content analysis. Three themes representing rationales emerged from the findings: self-governance over education, improvement of socio-economic conditions and sustainability. An underlying rationale that linked the three themes indicated that First Nations need recognition of self-government in order to control their education system, improve its quality and enhance learner outcomes.